THE EFFECTIVENESS OF APPLICATION OF GUIDED NOTE TAKING METHOD ON MATHEMATICS LEARNING OUTCOME IN STUDENTS MTs MUHAMMADIYAH KARANGKAJEN - Wisnu Cahya Nugraha; Uswatun Khasanah (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
The study of mathematics is still being dominated by teachers and several students who considered mathematic as an involute subject. The deficiency of variation in a particular subject may affect the student’s learning result in mathematics. The objective of this research is to examine the differentiation of learning outcome of mathematic study between students applying Guided Note Taking method and Expository method as well as determining the most effective one between students using Guided Note Taking method and Expository method towards in the 8th Grade Students of Muhammadiyah Karangkajen Islamic Junior High School, Yogyakarta. Population objected in this research are students Grade 8th ranging from the class of 8th A, 8th B, 8th C, 8th D, 8th E, Even Semester, Muhammadiyah Karangkajen Islamic Junior High School (MTs), Academic Term 2015/2016, with an exact total of 161 students. The sample in this research is students from the class of 8th A as an experimental class with an exact total of 31 students and students from the class of 8th C as controlling class with a total of 33 students selected by class appointment. The data collection techniques applied in this research are normality tests conducting a formula of Chi-Quadrate, homogeneity test with a formula–f  and hypothesis test with a formula of -t-test.  The result of a hypothesis test with a significant level 5% and latitude degree 62 pointed out that: (1) There is a difference in mathematics study which implemented the Guided Note Taking method and Expository method. This matter is explained at  = 3,4171 = 1,9996, therefore,  > and (2) Study by implementing Guided Note Taking method is more effective compared to the Expository method. This matter is explained at   = 3,4171 and   = 1,6698 therefore  >